HUBUNGAN TINGKAT PENDIDIKAN TERHADAP PENGGUNAAN LAKTAGOGUM - Dewi Sartika Siagian; Arum Meiranny; Sara Herlina; Ratih Ayuningtyas; Adelina Maryanti (LPPM Universitas Abdurrab, 2023)
Lactagogum is a drug that can increase or facilitate the production of milk. Synthetic lactagogums are not widely known and relatively expensive. This causes the need for alternative laktagogum drugs. Efforts to increase breast milk production can be done by carrying out early and routine breast care, improving breastfeeding techniques, or by consuming foods that can affect breast milk production. One of the reasons for the failure of exclusive breastfeeding is the perception of insufficient breast milk, which can be caused by physiological and psychological factors. Education is a very important factor in this life, which is why education is a very important business of all time. Increasing breast milk production can be done in various ways, one of which is increasing the intake of lactagogum. Lactagogum is a drug that can increase or facilitate the production of milk. The sample in this study were breastfeeding mothers who had babies ranging in age from 3 to 6 months spread throughout Indonesia. This study was conducted by distributing a questionnaire to assess education and the use of Lactagogue as a food to increase breast milk production. Dissemination of questionnaires can be done manually or via Google Drive links which are distributed to several regions in Indonesia. The purpose of this study was to determine the relationship between education and the use of laktagogums. The research results are there is a relationship between education and the use of Lactagogum. It is hoped that mothers who are in the process of breastfeeding can make efforts to increase milk production, one of which is by consuming Lactagogum.